Sistem Pendukung Keputusan Evaluasi Kinerja Pegawai Honorer Menggunakan Metode Simple Additive Weighting (SAW) di Pengadilan Negeri Pangkalan Balai - Rifai, Faisal (Jurnal Publikasi Teknik Informatika, 2025)
Honorary employees are an important element in supporting the performance of an institution. Their presence, with adequate competence and productivity, greatly helps ease the workload and ensures the smooth operation of government institutions. In this study, the implementation of a Decision Support System using the Simple Additive Weighting (SAW) method is applied to evaluate the performance of honorary employees. The results of this evaluation are expected to serve as a consideration for the Head of the Subdivision of Personnel in determining policies related to the provision of rewards, bonuses, or sanctions for honorary employees. In addition, calculations are also carried out on the assessment of non-government employees as a form of comparison. The SAW method was chosen because of its practical nature, ease of application, and ability to produce accurate decisions. This method works on the principle of weighted summation, where each criterion is assigned a specific weight, so that the final score obtained becomes the basis for decision-making. From a managerial perspective, performance evaluation can be enhanced by adding criteria according to the needs of the institution or company. Calculations using the SAW method have proven to provide a high level of accuracy in assessing the performance of honorary employees, particularly based on aspects of work, performance evaluation results, and work attitude assessment.